DEVELOPMENT OF A MECHATRONIC SYSTEM FOR BEDRIDDEN PEOPLE SUPPORT - Pereira, Filipe (2013)
This work is developed in the context of Ambient Assisted Living (AAL) and has, as main purpose, the development of a mechatronic system that allows caring of bedridden patients with ongoing medical care terminal (MCT), by a single person. This system allows higher autonomy in domiciliary care, safety, comfort and hygiene of bedridden patients. It contributes to a large increase in their quality of life as well as the ease of monitoring by providers of continuous care, which, in many cases, may be the family itself. The product includes an embedded processing interface for acquiring physiological data to support online monitoring. The development of this project was focused on improving the quality of life, autonomy, participation in social life and reducing healthcare costs in the area AAL. The developed societies currently face severe demographic changes: the world is aging at an unprecedented rate. In 2000, about 420 million people, or about 7 percent of the world population were over 65 years old. In 2050, that number will be near 1500 million people, about 16 percent of the world population. This demographic trend will be accompanied by the increase of people with physical limitations. This will impose new challenges for traditional health systems, not only for Portugal but also for all European countries. There is an urgent need to find solutions to improve the lives of people in their preferred environment by increasing their autonomy, self-confidence and mobility. Therefore, in the case of household scenarios, the provision of effective health services is of fundamental importance to the welfare and economic development of each country. This ongoing project aims to develop a mechatronic system to meet the diverse needs, namely: improving life, health care, safety, comfort, and remote monitoring of bedridden person.